PENGEMBANGAN MEDIA PEMBELAJARAN ASPEK KEBAHASAN TEKS OBSERVASI BERBASIS APLIKASI POWTOON KELAS X MAS PROYEK UNIVA MEDAN - Sri Ningsih; Rika Kartika; Nila Safina; Ratna Soraya (UNIVERSITAS DHARMAWANGSA, 2024)
This study aims to determine the development of feasibility and effectiveness of video learning media products on the Indonesian material